Comparison of different regimens of intravenous dexmedetomidine on duration of subarachnoid block - Anil Thomas; M. V. S Satyaprakash; Lenin Babu Elakkumanan; Prasanna Udupi Bidkar; Sandeep Kumar Mishra (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: Many studies have studied the effect of intravenous dexmedetomidine on the prolongation of the duration of the subarachnoid block (SAB). These studies had administered dexmedetomidine using different regimens. This study was designed to find out the suitable regimen with maximum advantages and minimum disadvantages. Material and Methods: Ninety-three ASA 1 and 2 patients scheduled to undergo surgeries under SAB were randomly allocated into three groups namely B, M, and BM. After SAB, Group B received 0.5 μg/kg of dexmedetomidine bolus over 15 min, Group M received 0.5 μg/kg/h of dexmedetomidine infusion until the end of surgery, Group BM received both bolus and infusion. Results: The time to achieve T10 sensory level (SL) was significantly faster in the Groups B and BM than in the Group M. Maximum block height achieved was T4 and was same in all the groups. The Time to achieve maximum SL and Bromage 3 was comparable in all groups. The two-segment regression time and time to reach Bromage 0 was significantly higher in Groups M and BM than Group B. The time for a first request of analgesia was similar in Groups M and BM. The maximum sedation attained in all groups was Ramsay Sedation Score of 3. Side effects such as bradycardia, hypotension, and desaturation were comparable between the groups. Conclusion: We conclude that the continuous infusion of dexmedetomidine results in more advantages than just a bolus dose. Therefore, we suggest using only the maintenance dose of intravenous dexmedetomidine after subarachnoid blockade for prolonging the duration and achieving sedation.